Pengaruh Eksperimen Light Shelf terhadap Pencahayaan Alami pada Ruang Kerja - Tiono, Evan Prabowo (Intra, 2015)
The utilization of light shelf system can help enlighting space with natural lighting, while reducing lamp usage and encourage energy saving. In addition, it can also help reducing excess glare in the room, because that is the main problem when someone is working in an office during the day.This research was done to determine the function of light shelf system towards workspace using experiment method which then simulated using the software Ecotect 2011 to determine the level of illumination in the room. The experiment was done by creating 3 variant light shelf shapes. Simulation was done to determine the function of each light shelf and to change the position according to the researcher.The result was made into a graph and table to compare the effectivity of each light shelf function with each position. The result was then compared with the standard of workspace illumination from SNI. Researcher chose one best result that meets or come the closest to the standard. Â The second shape of light shelf gave the best result. It has tilt planes on both top and bottom inside with positioning inside-middle on the window.